2016
DOI: 10.1002/aoc.3538
|View full text |Cite
|
Sign up to set email alerts
|

Transfer hydrogenation of aryl ketones with homogeneous ruthenium catalysts containing diazafluorene ligands

Abstract: Novel cationic ruthenium(II) complexes bearing a 4,5‐diazafluorene unit and p‐cymene as ligands have been synthesised. The complexes were characterised based on elemental analysis and Fourier transform infrared and nuclear magnetic resonance spectroscopies. The synthesised Ru(II) complexes were employed as pre‐catalysts for the transfer hydrogenation of aromatic ketones using 2‐propanol as both hydrogen source and solvent in the presence of NaOH. All complexes showed high catalytic activity as catalysts in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In their work, Song and co-workers have found that the acidic C-H bonds of daf can undergo deprotonation that results in follow-up reactivity [16][17][18][19][20]. More broadly, Stahl [21][22][23] and several other groups [24][25][26] have developed a number of catalyst systems supported by diazafluorene ligands. In all these cases, daf and its derivatives seem to play a decisive role in enabling unique chemistry, confirming the usefulness of the ligands as a counterpoint to the more common R bpy family.…”
Section: Introductionmentioning
confidence: 99%
“…In their work, Song and co-workers have found that the acidic C-H bonds of daf can undergo deprotonation that results in follow-up reactivity [16][17][18][19][20]. More broadly, Stahl [21][22][23] and several other groups [24][25][26] have developed a number of catalyst systems supported by diazafluorene ligands. In all these cases, daf and its derivatives seem to play a decisive role in enabling unique chemistry, confirming the usefulness of the ligands as a counterpoint to the more common R bpy family.…”
Section: Introductionmentioning
confidence: 99%
“…4,5-Diazafluorene ( daf ) and 4,5-diazafluoren-9-one ( dafo , Scheme 1) can be considered as analogues of bipy , as they contain the 2,2-bipyridine fragment that makes them suitable for N , N -chelating coordination. 15–35 However, the pyridyl groups in daf and dafo are additionally tied together by a –CH 2 – or a CO group, respectively. This leads to larger distances between the donor atoms than that of bipy and, therefore, enforces larger bite angles.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of these ligands for coordination chemistry was recognized much later than for bipy , and therefore, metal complexes with daf and dafo derivatives have been explored to a much lesser extent. 15–35…”
Section: Introductionmentioning
confidence: 99%